Grassroots Professional Development: How Teachers Use Twitter - Forte, Andrea; Humphreys, Melissa; Park, Thomas (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
In an exploratory study, we used survey, interviews and content analysis techniques to understand how educators appropriate Twitter and other social media in their practice. We report on teachers’ use of Twitter, structural features of their on and offline professional networks, and the institutional policies that shape their appropriation of social media for professional use. Most importantly, our analysis suggests teachers on Twitter tend to be eager adopters of technologies and well positioned to broker information as bridges between members of their local communities of practice and other networks of educators. Based on these findings, we discuss teachers on Twitter as participants in grassroots professional development efforts and the potential for them to be powerful fomenters and enactors of reform in educational communities.